A compendium of G-protein–coupled receptors and cyclic nucleotide regulation of adipose tissue metabolism and energy expenditure. Issue 5 (9th March 2020) - Ceddia, Ryan P.; Collins, Sheila
Abstract: With the ever-increasing burden of obesity and Type 2 diabetes, it is generally acknowledged that there remains a need for developing new therapeutics. One potential mechanism to combat obesity is to raise energy expenditure via increasing the amount of uncoupled respiration from the mitochondria-rich brown and beige adipocytes. With the recent appreciation of thermogenic adipocytes in humans, much effort is being made to elucidate the signaling pathways that regulate the browning of adipose tissue. In this review, we focus on the ligand–receptor signaling pathways that influence the cyclic nucleotides, cAMP and cGMP, in adipocytes. We chose to focus on G-protein–coupled receptor (GPCR), guanylyl cyclase and phosphodiesterase regulation of adipocytes because they are the targets of a large proportion of all currently available therapeutics. Furthermore, there is a large overlap in their signaling pathways, as signaling events that raise cAMP or cGMP generally increase adipocyte lipolysis and cause changes that are commonly referred to as browning: increasing mitochondrial biogenesis, uncoupling protein 1 (UCP1) expression and respiration.